Influence of incident beam polarization on intensity and polarization distributions of tight focusing spot. (January 2015) - Li, Qinggele; Ledoux-Rak, Isabelle; Lai, Ngoc Diep
Abstract : We demonstrated theoretically and experimentally the influence of polarization of an input light beam on the intensity and polarization distributions of a tight focusing spot, obtained by a high numerical aperture (NA) objective lens (OL). The numerical calculations, based on vectorial Debye theory, show that, under tight focusing condition (NA = 1.4), the shape of the focusing spot varies as a function of the input beam polarization, resulting in either asymmetric or symmetric spots. A home made confocal microscope constituted by a high NA OL is employed to scan the fluorescence image of single gold nanoparticles showing the actual polarization dependence of focusing spot. The input linear polarization allows generating a small but asymmetric focusing spot, while the circular polarization produces a larger but symmetric one.